Ecological networks of grassland plants and arthropods - Welti, Ellen A. R. (Kansas State University, 2017)
Ecological communities are comprised both of species and their interactions. The importance of species interactions is embraced by ecological network analysis, a framework used to identify non-random patterns in species interactions, and the consequences of these patterns for maintaining species diversity. Here, I investigated environmental drivers of the structure of plant-pollinator and plant-herbivore networks. Specifically, I asked: (1) Do global-scale climate gradients shape mutualistic and antagonistic networks? (2) At a landscape scale (within a 3,487 ha research site), how do contrasting regimes of major grassland disturbances - fire frequency and grazing by bison (Bison bison) - shape plant-pollinator network structure? (3) How do fire and grazing affect plant-grasshopper network structure? And, (4) What is the role of plant species diversity in determining plant-herbivore network structure? At the global scale, variability in temperature was the key climatic factor regulating both antagonistic and mutualistic network structural properties. At the landscape scale, fire and grazing had major consequences for plant-pollinator and plant-herbivore communities. In particular, bison grazing increased network complexity and resistance to species loss for both plant-pollinator and plant-herbivore systems. Results from an experimental grassland restoration that manipulated plant diversity suggest that plant diversity directly affects plant-herbivore structure and increases network stability. Collectively, these results suggest that environmental gradients and plant species diversity regulate the network structure of ecological communities. Determining how the structure of ecological interactions change with environmental conditions and species diversity improves our ability to identify vulnerable communities, and to predict responses of biodiversity to global change.
Keywords: Ecology; Ecological network; Tallgrass prairie; Food web; Pollinator; Herbivore